The Protective Effect of Limosilactobacillus fermentum FZU501 Against Alcohol-Induced Liver Injury in Mice via Gut Microbiota–Liver Axis - Zihua Liang; Shiyun Chen; Xiangchen Zhang; Jiayi Li; Weiling Guo; Li Ni; Xucong Lv (Foods)
As a probiotic strain isolated from Hongqu rice wine (a traditional Chinese fermented food), Limosilactobacillus fermentum FZU501 (designated as Lf) demonstrates exceptional gastric acid and bile salt tolerance, showing potential application as a functional food. The aim of this study was to investigate the protective effect of dietary Lf intervention on alcohol-induced liver injury (ALI) in mice. The results demonstrated that oral administration of Lf effectively ameliorated alcohol-induced lipid metabolism disorders by reducing the serum levels of TC, TG and LDL-C and increasing the serum levels of HDL-C. In addition, oral administration of Lf effectively prevented alcohol-induced liver damage by increasing the hepatic activities of antioxidant enzymes (CAT, SOD, GSH-Px) and alcohol-metabolizing enzymes (ADH and ALDH). Interestingly, 16S amplicon sequencing showed that oral administration of Lf increased the number of Prevotella, Lachnospiraceae_NK4A136_group and Lactobacillus, but decreased the proportion of Faecalibaculum, Adlercreutzia and Alistipes in the intestines of mice that consumed excessive alcohol, which was highly associated with improved liver function. As revealed by liver untargeted metabolomics studies, oral Lf clearly changed liver metabolic profiles, with the signature biomarkers mainly involving purine metabolism, taurine metabolism, tryptophan, alanine, aspartic acid and glutamate metabolism, etc. Additionally, Lf intervention regulated liver gene transcription in over-drinking mice for cholesterol metabolism, bile acid metabolism, fatty acid β-oxidation, alcohol metabolism and oxidative stress. Taken together, the above research results provide solid scientific support for the biological activity of Lf in ameliorating alcohol-induced liver metabolism disorder and intestinal microbiota imbalance.